Communication Via Social Media: How Employees Will Paradoxically Support the Organization while Putting Less Effort at Work. (April 2023) - Labban, Alice; Bizzi, Lorenzo
Research on the effects of social media use by employees on work behaviors is inconclusive and showed mixed findings. To bring clarity to the extant literature, instead of focusing on generic social media use, we focus on a specific social media behavior—communication via social media with coworkers and friends—and theorize that it simultaneously triggers positive and negative effects on work behaviors through the mediation of opposite emotions. More specifically, our empirical study shows that employee communication via social media leads simultaneously to positive behaviors, predicting organizational citizenship behaviors, and negative behaviors, predicting counterproductive work behaviors. Happiness mediates the relationship between communication with social media and organizational citizenship behavior. Fatigue mediates the relationship between communication with social media and counterproductive work behaviors. The negative effects are stronger for communication with friends while the positive effects are more pronounced for communication with colleagues. Results are particularly revealing. Paradoxically, communication via social media makes employees happy and tired at the same time, making them likely to support the organization and coworkers while simultaneously working in counterproductive manner.